Cultivating Moral Culture:The Endeavors of Madrasah Ibtidaiyah - Musyarrafah Sulaiman Kurdi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2023)
The research explores the growing concern about the lack of ethical behavior and values globally and the need for moral education, particularly in the context of Islamic education. It focuses on Madrasah Ibtidaiyah in Indonesia and its efforts to cultivate a moral culture among its students through its curriculum, pedagogy, and community engagement. The research aims to explore the ethical values emphasized in its education and compare the experiences of its students and alumni with those who have received a secular education. The research methodology involves a literature review to gather and analyze data from various sources. The study examines the role of curriculum and pedagogy in Madrasah Ibtidaiyah, emphasizing the integration of Islamic values into various subjects and the emphasis on character development. It also explores the school's community engagement efforts, including partnerships with families, religious leaders, and local institutions to reinforce ethical values. The text compares the experiences of Madrasah Ibtidaiyah students and alumni with those of secular education, highlighting differences.